Pengaruh Bahan Ajar Berbasis Sastra Anak Kontemporer Terhadap Penguatan Literasi dan Pendidikan Karakter - Prima Nucifera; Maulida Sari; Tanita Liasna (CV. Global Cendekia Inti, 2026)
This study aims to determine the effect of contemporary children's literature-based teaching materials on strengthening literacy and character education in students. This study is motivated by the importance of literacy culture, especially for students. Literacy culture is closely related to character education in students. This study was conducted at SD Negeri Birem Puntong, located in Buket Meudang Ara Village, Langsa Timur Subdistrict, Langsa City, Aceh Province, at the end of the second semester of the 2024/2025 academic year. The method used in this study was a quasi-experimental design with a non-equivalent control group design. The subjects in this study consisted of two groups: an experimental group and a control group. The instruments used in this study included literature-based teaching materials, literacy tests, character education questionnaires, observations, and interviews. The results of the study showed a significant increase in the average literacy and character education scores in the experimental group. This was demonstrated by the pre-test and post-test results, which showed a higher average score in the experimental group. From the results of this study, it can be seen that the hypothesis was proven through a paired sample t-test with a significance level of α=0.05, yielding a sig value (2-tailed) of 0.000 < 0.05. This means that there is a significant effect of the use of contemporary children's literature-based teaching materials on strengthening literacy and character education.